A degradable fluorinated surfactant for emulsion polymerization of vinylidene fluoride. Issue 81 (25th September 2018) - Banerjee, Sanjib; Schmidt, Judith; Talmon, Yeshayahu; Hori, Hisao; Asai, Takuma; Ameduri, Bruno
Abstract : An original degradable fluorinated surfactant, 3-hydroxy-2-(trifluoromethyl)propanoic acid was applied for the emulsion polymerization of vinylidene difluoride (VDF) to yield a latex of PVDF, consisted of typically 100 nm particle diameters. Abstract : An original degradable fluorinated surfactant, 3-hydroxy-2-(trifluoromethyl)propanoic acid (MAF-OH), was applied for the emulsion polymerization of vinylidene fluoride (VDF) to yield a latex of PVDF, consisting of typically 100 nm particle diameters. This surfactant was shown to be easily decomposed in subcritical water, releasing fluoride anions. The % reversed head-to head (H–H) addition is greatly minimized (2.4%) in the PVDF, prepared in the presence of MAF-OH surfactant.